Early retirement and economic incentives - Erik Hernæs; Marte Sollie; Steinar Strøm (University of Oslo, Department of Economics, 1999)
In Norway early retirement programs have gradually reduced the retirement age from 67 to 62 for a majority of the labor force. Based on micro data for 1990 and 1992, we estimate a competing risk models with three states: full retirement, partial retirement/part-time work, and full-time work, and we use the estimated model in simulations to study how financial incentives can be strengthened to extend working life. Both financial incentives, educational background and industry affiliation is found to influence retirement behavior. For low and middle incomes, the tax system shifts the incentives heavily towards retirement, in particular partial retirement combined with part-time work.
Keywords: 330; Early retirement; multinomial logit model; taxes; Flexible Altersgrenze; Steuerbegünstigung; Ökonomischer Anreiz; Norwegen; Logit-Modell